Hubungan antara Self-Efficacy dengan Prokrastinasi Akademik dalam Menyelesaikan Skripsi pada Mahasiswa Fakultas Psikologi - Jenny Monica; Mulia Siregar (Universitas Medan Area, 2023)
This article aims to see the relationship between self-efficacy and academic procrastination in completing thesis on students at the Faculty of Psychology UMA. The problem is focused on self-efficacy and academic procrastination only. In order to approach this problem, the theoretical reference from Bandura and MC Crown is used. The data were collected through a Likert scale and analyzed quantitatively. Sampling techniques and data using. There are two Likert scales, namely the self-efficacy scale and academic procrastination. Sampling using purposive sampling technique, with a total sample of 85 students of the Faculty of Psychology UMA who are completing their thesis. The data analysis test using the Kolmogorov-Smirnov technique (rxy) obtained a result of 0.968 with a significance of p = 0.000 0.050. This means that the hypothesis is accepted, namely that there is a negative relationship between self-efficacy and academic procrastination in students of the Faculty of Psychology UMA who are completing their thesis. Self-efficacy is classified as low where the hypothetical mean = 92.5 empirical mean = 91.70 and the difference exceeds the SD number = 22.58. Academic procrastination is high where the hypothetical mean = 87.5 empirical mean = 113.30 and the difference exceeds the SD number = 14.22. The coefficient of the determinant of the correlation is r2 = 0.937. This study concludes that self-efficacy contributes effectively to academic procrastination by 93.7%.